Corporate Social Responsibility, Konservatisme Akuntansi, Timeliness dan Earning Rensponse Coefficient dengan Leverage sebagai Variabel Moderasi - Holiawati Holiawati; Astri Melani Rizky; Endang Ruhiyat (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
The aim of this research is to determine the effect of corporate social responsibility, accounting conservatism and timeliness and then leverage it as a moderate variable toward earning response coefficient in consumer goods sub-sector manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during 2016-2019. This research is a quantitative study with 28 total samples which is there are 112 data researched. Based on the T-test it result is known that the accounting conservatism variable and leverage-moderated corporate social responsibility variable affect toward earning response coefficient. The timeliness variable and leverage-moderated timeliness have a negative influence on the earning response coefficient. Meanwhile, the corporate social responsibility variable and the leverage-moderated accounting conservatism are not affected by the earning response coefficient